Prevalence of subclinical atherosclerosis and risk of atherosclerotic cardiovascular disease in older adults living with HIV - Linda Aurpibul (2020)
© Copyright 2019, Mary Ann Liebert, Inc. Cardiovascular disease (CVD) is one among the leading causes of mortality in people living with HIV on antiretroviral treatment (ART) worldwide. We examined the prevalence of subclinical atherosclerosis, associated factors, and risk of CVD in older adults living with HIV (OALHIV). A cross-sectional study was conducted with patients aged ≥50 years with HIV infection receiving ART at community hospitals in Chiang Mai, Thailand. Age- and sex-matched patients without documented HIV infection who visited the general outpatient department were enrolled for comparison. Cardio-ankle vascular index (CAVI) and ankle-brachial index (ABI) were measured using the vascular screening system, VaSera System™ (Fukuda Denshi Co., Ltd., Japan) to determine subclinical atherosclerosis (defined as CAVI ≥9.0) and peripheral arterial disease (defined as ABI <0.9), respectively. The Ramathibodi-Electric Generating Authority of Thailand (RAMA-EGAT) scores to predict the risk of coronary stenosis and the 10-year risk of ASCVD by pooled cohort equation were calculated. One hundred fifty-five patients were enrolled (107 HIV/48 comparison). The mean age was 59.0 years (SD 6.1); 67 (43%) were male. Participants in the HIV and comparison group were similar with respect to abnormal CAVI (57% vs. 58%, p = .88), abnormal ABI (6% vs. 8%, p = .50), and the risk of coronary stenosis (34% vs. 44%, p = .23). However, the 10-year risk of ASCVD was lower in HIV than in the comparison group (29% vs. 48%, p = .02). In OALHIV, diabetes mellitus was the only factor associated with abnormal CAVI. The cardiovascular risk among OALHIV in this study was similar to non-HIV population. More than a half of them had abnormal CAVI, and approximately one-third was at ≥10% 10-year risk of ASCVD.